2006
DOI: 10.1002/app.24820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cationic group content on shape memory effect in segmented polyurethane cationomer

Abstract: To illustrate the importance of cationic groups within hard segments on shape memory effect in segmented polyurethane (PU) cationomers, the shape memory polyurethane (SMPU) cationomers composed of poly(e-caprolactone) (PCL), 4,4 0 -diphenylmethane diisocyanate (MDI), 1,4-butanediol (BDO), and N-methyldiethanolamine (NMDA) or N,N-bis(2-hydroxyethyl)isonicotinamide (BIN) were synthesized. The comparison of shape memory effect between NMDA series and BIN series was made. The relations between the structure and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 33 publications
1
28
0
Order By: Relevance
“…These soft segment and hard segment were used because several reasons: first, generally, the obtain polyurethane possess high mechanical and processing properties [15,28,35]; second, PCL is a type of biomaterial with good biocompatibility, non-toxicity [2,36]; third, more importantly, it has a melting transition at about 50 • C which is in the range of the operating temperature (45-70 • C) [20,21,23,24]. The materials' thermal/mechanical, stress-strain behavior, shape memory effect and softening and hardening process were studied.…”
Section: Introductionmentioning
confidence: 99%
“…These soft segment and hard segment were used because several reasons: first, generally, the obtain polyurethane possess high mechanical and processing properties [15,28,35]; second, PCL is a type of biomaterial with good biocompatibility, non-toxicity [2,36]; third, more importantly, it has a melting transition at about 50 • C which is in the range of the operating temperature (45-70 • C) [20,21,23,24]. The materials' thermal/mechanical, stress-strain behavior, shape memory effect and softening and hardening process were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Adding ionic groups as chain extenders alters the phase separated hard segment domains of segmented SMPUs and the thermal characteristics of the soft segment and has been reported for both cation and anion based ionomers. For example, Zhu et al examined the influence of N, N‐bis(2‐hydroxyethyl)isonicotinamide (BINA) concentration on the thermal and thermomechanical behavior of PCL based SMPU cationomers bearing 4,4′‐diphenylmethane diisocyanate (MDI) hard segments. It was observed that the dynamic rubbery modulus and the tensile stress at 100% elongation decreased for up to 8 wt % BINA concentration indicating destabilization of hard segments.…”
Section: Smps Based On Non‐covalent Rbgsmentioning
confidence: 92%
“…Incorporating ionic groups into segmented polyurethanes provides an opportunity to alter the thermal stability, glass transition, mechanical behavior, and dilute solution properties . Adding ionic groups as chain extenders alters the phase separated hard segment domains of segmented SMPUs and the thermal characteristics of the soft segment and has been reported for both cation and anion based ionomers. For example, Zhu et al examined the influence of N, N‐bis(2‐hydroxyethyl)isonicotinamide (BINA) concentration on the thermal and thermomechanical behavior of PCL based SMPU cationomers bearing 4,4′‐diphenylmethane diisocyanate (MDI) hard segments.…”
Section: Smps Based On Non‐covalent Rbgsmentioning
confidence: 99%
“…PUIs have been synthesized by a number of methods including polymerization using ionic isocyanates or diols or post‐polymerization modification to introduce ionic functionality . Using semi‐crystalline soft‐segments a number polyurethane ionomers (PUIs) have been prepared using an ion‐containing, or easily modified, diol as a chain extender and their shape memory properties have been investigated …”
Section: Polyurethane and Polyester Ionomersmentioning
confidence: 99%